Design and simulation of a lower limb exoskeleton with linear electric actuators - Grzelczyk, Dariusz; Jarzyna, Olga; Awrejcewicz, Jan (Wydawnictwo Politechniki Łódzkiej, 2021)
In the present study, we proposed and investigated a relatively simple and inexpensive construction of a lower limb exoskeleton driven by linear electric actuators and controlled by an Arduino microcontroller board. Moreover, to study crucial kinematic and dynamic parameters of the proposed device, we developed a general, three-dimensional simulation model of the exoskeleton in Mathematica software. To control individual joints of the investigated exoskeleton, we employed time histories of human joint angles in normal gait, recorded with the use of a motion capture system. As a result, we developed a novel human gait generator, which can be used to produce rhythmic movements in hip, knee and ankle joints of both limbs. Finally, the developed control approach was verified with the use of the constructed prototype of the exoskeleton.
Keywords: human lower limbs; exoskeleton; human movement; ludzkie kończyny dolne; egzoszkielet; ruch człowieka